Neuroprotective Effect of 4-Methylcyclopentadecanone on Focal Cerebral Ischemia/Reperfusion Injury in Rats - Yukui Ma; Yue Li; Chunxia Zhang; Xiaomian Zhou; Yingliang Wu (Elsevier, 2014)
Abstract.: The present study aimed to investigate the effect of 4-methylcyclopentadecanone (4-MCPC) on local cerebral ischemia-reperfusion and the possible mechanisms involved. For this purpose, the focal cerebral ischemia rat model was induced by middle cerebral artery occlusion (MCAO) for 2 h, and the rats were treated with 4-MCPC (4 or 8 mg·kg−1, p.o.) just 0.5 h before reperfusion. The neurological deficit scores and the ischemic infarct volume were recorded 24 h after the MCAO. In addition, the number of apoptotic cells was measured by TUNEL assay, and the expression of apoptosis-regulatory proteins and the PI3K/Akt neuroprotective signaling pathway were investigated by western blotting. Our results indicated that 4-MCPC (4 or 8 mg·kg−1) remarkably alleviated cerebral I/R injury by decreasing infarct volume and neurological deficit scores. 4-MCPC also decreased the number of apoptotic cells, regulated the expression of Bcl-2 and Bax, and increased the ratio of Bcl-2/Bax. Further study revealed that 4-MCPC treatment also increased the level of p-Akt and p-GSK-3β. Wortmannin (PI3K inhibitor) markedly abolished the effects of 4-MCPC. Taken together, our results suggest that 4-MCPC protects against cerebral I/R injury through the inhibition of apoptosis, and this neuroprotective effect may be partly related to the activation of the PI3K/Akt signal pathway. Keywords:: 4-methylcyclopentadecanone, apoptosis, Akt, GSK-3β, ischemia/reperfusion